Analysis of Factors Affecting Public Trust in Hospital Inpatient Services rantaup Meetings - Yanci Akmal Ibon Sagala; Arifah Devi Fitriani; Mappeaty Nyorong (Jurnal Perilaku Kesehatan Terpadu, 2025)
The health service industry has a pretty good prospect and future, where currently health services are no longer just focused on treating a disease, but health services have developed and include providing services to the community in efforts to prevent and improve health. There is a decrease in patients due to decreased patient trust in hospital services. The purpose of the research is to find out the analysis of factors that influence public trust in inpatient services at Rantauprapat Hospital. This type of research is analytic observational using a cross sectional study design. The population was patients/families of inpatients at Rantauperapat Hospital with a sampling technique using cluster random sampling totaling 95 respondents. The data used includes primary data and secondary data. Data analysis using the T test and f test. The results of this study indicate that the physical support variable obtained a calculated value = 3.510 with sig = 0.001 <0.05, a sig result of 0.001 <0.05, personal contact obtained a calculated value = 2.420 with a sig = 0.018 <0.05. The results of the Anova statistical test obtained an F value = 62,583 with a sig value = 0.000 <0.05 and there was a simultaneous effect of physical support and personal contact on public trust in the inpatient service of Rantauprapat Hospital. Based on the results, the magnitude of r2 contact personal is 48.01% and physical support is 45.09%, which is obtained from the partial correlation coefficient. This shows that the contact personal variable has a greater influence on public trust in inpatient services at Rantauprapat Hospital compared to the physical support variable. It is suggested to the leadership to evaluate the performance of the services of doctors and other health workers, such as being professional and working in accordance with the SPO so as to increase patient confidence.